Evaluation of the efficacy of high molecular weight hyaluronic acid with chondroitin sulfate in post-traumatic knee osteoarthritis - E. I. Bialik; M. A. Makarov; V. A. Nesterenko; V. E. Bialik; A. E. Karateev; A. A. Bialik; V. I. Stadnik (Современная ревматология)
Objective: to evaluate the efficacy of a single or double administration of a preparation of high molecular weight hyaluronic acid (HLA) with chondroitin sulfate (CS) in post-traumatic knee osteoarthritis (OA). Material and methods. The study included 91 patients with stage III post-traumatic knee OA. All patients received intra-articular (i/a) injection of high molecular weight HLA with CS; 36 patients received the drug once (group 1) and 55 twice (group 2) with an average interval of 7±2 days. Before the start of treatment and 2 weeks, 1, 3, 6 and 12 months after i/a injection of HLA, pain intensity at rest and during movement was assessed using a visual analogue scale (VAS) and function was assessed using KOOS questionnaire (Knee injury and Osteoarthritis Outcome Score). Results and discussion. In general, patients receiving single and double i/a injections of HLA, pain during movement at baseline, and after 2 weeks, 1, 3, 6 and 12 months was 6.7±1.1; 4.0±0.7; 4.3±0.8; 4.6±1.0; 4.5±1.1 and 5.3±0.4 cm; pain at rest – 2.7±0.6; 1.5±0.2; 1.8±0.2; 2.1±0.5; 2.2±0.3 and 2.6±0.2 cm, and KOOS score was 35.9±13.6; 43.5±13.6; 49.2±17.6; 57.0±12.5; 51.5±11.7 and 40.3±10.2, respectively. In group 1, pain during movement at the same time line reached 6.7±1.2; 4.0±0.7; 4.3±1.1; 4.6±.08; 4.5±0.6 and 5.3±1.3 cm; pain at rest – 2.7±0.5; 1.5±0.3; 1.8±0.4; 2.1±0.4; 2.2±0.6 and 2.6±0.6 cm; KOOS score – 37.2±8.7; 39.1±10.1; 43.0±12.3; 47.0±13.6; 49.5±14.7 and 35.7±12.4, respectively.In the 2nd group, pain during movement was 6.1±1.5; 3.3±0.7; 3.6±0.6; 3.4±0.5; 3.7±0.4 and 4.4±0.3 cm; pain at rest was 2.6±0.3; 1.9±0.2; 1.1±0.2; 0.9±0.1; 0.7±0.1 and 1.7±0.3 cm; KOOS score was 34.7±9.4; 47.1±11.1; 59.3±11.5; 61.4±12.7; 57.2±14.3 and 45.7±12.4, respectively. Conclusion. In patients with stage III knee OA, double injections of HLA with HS were more effective. The maximum pain reduction and functional improvement were observed in the first 3 months after local injection therapy.